2013
DOI: 10.1155/2013/648257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Traditional Chinese Herbal Medicine with Antiquorum Sensing Activity onPseudomonas aeruginosa

Abstract: Traditional Chinese herbal medicines (TCHMs) were tested for their ability of antiquorum sensing. Water extracts of Rhubarb, Fructus gardeniae, and Andrographis paniculata show antiquorumsensing activity when using Chromobacterium violaceum CV12472 as reporter; the sub-MIC concentrations of these TCHMs were tested against AHL-dependent phenotypic expressions of PAO1. Results showed significant reduction in pyocyanin pigment, protease, elastase production, and biofilm formation in PAO1 without inhibiting the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Quercetin, which exists in many fruits, vegetables and grains, is a plant polyphenol. It was reported to significantly inhibit biofilm formation and production of virulence factors including pyocyanin, protease and elastase at a lower concentration compared with that for most previously reported plant extracts and substances [44][45][46][47]. Further investigation of the transcriptional changes associated with QS found that the expression levels of LasI, LasR, RhlI and RhlR involved in QS signaling were significantly reduced [48].…”
Section: Quercetinmentioning
confidence: 95%
“…Quercetin, which exists in many fruits, vegetables and grains, is a plant polyphenol. It was reported to significantly inhibit biofilm formation and production of virulence factors including pyocyanin, protease and elastase at a lower concentration compared with that for most previously reported plant extracts and substances [44][45][46][47]. Further investigation of the transcriptional changes associated with QS found that the expression levels of LasI, LasR, RhlI and RhlR involved in QS signaling were significantly reduced [48].…”
Section: Quercetinmentioning
confidence: 95%
“…DMSO and penicillic acid were used as negative and positive controls, respectively. After 18 h of incubation at 37°C, the protease activity was determined by a skim milk plate assay (Chu et al, 2013 ). Briefly, 100 μL of cell free supernatant of treated (extracts and penicillic acid) and untreated (negative control) PAO1 was loaded in each well containing Muller Hinton Agar with 2% skim milk and was incubated at 37°C for 24 h. Protease activity was evidenced by the presence of a zone of casein hydrolysis surrounding the well.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of modern drugs either belongs to natural products or originate from them (Li and Vederas, 2009 ), with marine sponges being one of the most prolific sources of chemical diverse bioactive natural products (Blunt et al, 2015 ). These compounds have been studied in respect to chemical ecology and provide the sponge with defense against predation, fouling, and pathogen attack (e.g., Chu et al, 2013 ; Rohde et al, 2015 ). From a biotechnology perspective, these compounds can have a broad spectrum of action comprising anti-inflammatory, anticancer, and immune-modulating activities (e.g., Costantino et al, 2008 , 2009 ; Mayer et al, 2010 ; Teta et al, 2013 ; Blunt et al, 2015 ; Kaufman et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, traditional Chinese drugs and food have attracted considerable attention because of their unique antibacterial properties (Chu et al . ; Li et al . ).…”
Section: Introductionmentioning
confidence: 99%